2018
DOI: 10.33541/jet.v4i3.854
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Language Learners’ Anxiety in Language Skills Learning: A Case study at Universitas Kristen Indonesia

Abstract: Anxiety has been a matter of substantial concern in foreign language (FL) learning setting for educators since it is a major obstacle learners need to overcome (Ellis, 2008; Wu, 2010).This study was aimed at finding out students’ language anxiety in learning the four language skills at a university level in English as a FL context. The participants were 71 students of the English education Department of Universitas Kristen Indonesia. Data was collected by administering a set of questionnaire. To support the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
(34 reference statements)
2
13
0
Order By: Relevance
“…Peer interaction influence on the students anxiety level. It is in line with the statement of (Nawas, 2020) and (Male, 2018) asserting that when language learners speak a second language without stress or worry, they convey their thoughts and ideas in an ordered, clear, and acceptable manner. Language learners, on the other hand, articulate their thoughts and deliver messages with a sense of perplexity that is difficult for listeners to comprehend if they lack selfconfidence, or are in a condition of high anxiety (Amiruddin & Jannah, 2022b).…”
Section: Resultssupporting
confidence: 88%
“…Peer interaction influence on the students anxiety level. It is in line with the statement of (Nawas, 2020) and (Male, 2018) asserting that when language learners speak a second language without stress or worry, they convey their thoughts and ideas in an ordered, clear, and acceptable manner. Language learners, on the other hand, articulate their thoughts and deliver messages with a sense of perplexity that is difficult for listeners to comprehend if they lack selfconfidence, or are in a condition of high anxiety (Amiruddin & Jannah, 2022b).…”
Section: Resultssupporting
confidence: 88%
“…A study that captured the face of Indonesian distance learning only exposed the instructional media and technologies being utilized in the learning process (Yaumi, 2007). Whereas, the study of anxiety in Indonesia typically concentrated on the relation of anxiety with speech production (Anandari, 2015), gender differences (Nurhaeni, 2019), four basic skills (reading, writing, speaking, and listening) (Male, 2018) and its impact on language learning (Budiman, Ngadiso, & Suparno, 2017). The study of anxiety in distance learning especially in the time of crisis, like the outbreak of Covid-19 is found rare.…”
Section: Introductionmentioning
confidence: 99%
“…The research on listening anxiety, however, is still limited (i.e. Izzah & Keeya, 2019;Male, 2018) . Male (2018) using FLCAS investigated all four-skills language anxiety.…”
Section: E-issn 2541-0075 13mentioning
confidence: 99%
“…Izzah & Keeya, 2019;Male, 2018) . Male (2018) using FLCAS investigated all four-skills language anxiety. In listening anxiety particularly, he found that Indonesian university students learning English experience listening anxiety, especially when they could not understand the words or when they have to hear a longer text.…”
Section: E-issn 2541-0075 13mentioning
confidence: 99%